2020
DOI: 10.1111/aas.13751
|View full text |Cite
|
Sign up to set email alerts
|

Arterial and end‐tidal carbon dioxide partial pressure difference during prehospital anaesthesia in critically ill patients

Abstract: Background Normoventilation is crucial for many critically ill patients. Ventilation is routinely guided by end‐tidal capnography during prehospital anaesthesia, based on the assumption of the gap between arterial partial pressure of carbon dioxide (PaCO2) and end‐tidal carbon dioxide partial pressure (PetCO2) of approximately 0.5 kPa (3.8 mmHg). Methods We retrospectively analysed the airway registry and patient chart data of patients who had been anaesthetised and intubated endotracheally by the prehospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Two recent publications investigated the CO 2 gap in critically ill patients after prehospital emergency anesthesia [25,26]. Their ndings are in line with our results and showed only moderate correlation between EtCO 2 and PaCO 2 , con rming that EtCO 2 alone should be used with caution to guide ventilation in the critically ill.…”
Section: The Co 2 Gapsupporting
confidence: 90%
“…Two recent publications investigated the CO 2 gap in critically ill patients after prehospital emergency anesthesia [25,26]. Their ndings are in line with our results and showed only moderate correlation between EtCO 2 and PaCO 2 , con rming that EtCO 2 alone should be used with caution to guide ventilation in the critically ill.…”
Section: The Co 2 Gapsupporting
confidence: 90%
“…Two recent publications investigated the CO 2 gap in critically ill patients after prehospital emergency anesthesia 25 , 26 . Their findings are in line with our results and showed only moderate correlation between EtCO 2 and PaCO 2 , confirming that EtCO 2 alone should be used with caution to guide ventilation in the critically ill.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies were mainly conducted in the ICU; researchers studied participants exposure to hyperoxaemia for several hours or even days. Henry et al 29 found that early hyperoxaemia (>40 kPa) happening less than two hours from hospital admission was not associated with increased hospital mortality. However, hyperoxaemia occurring later was associated with poor outcomes.…”
Section: Discussionmentioning
confidence: 98%